PROLACTIN FUNCTION IN ZEBRAFISH DEVELOPMENT - Nguyen, Nhu (East Carolina University, 2010)
Extensive studies have implicated a myriad of functional roles for prolactin (PRL) and prolactin receptor (PRLR) across a variety of adult vertebrate species. However, much less is known about the physiological role(s) of PRL during embryonic/fetal development. Previously, we demonstrated that in vivo knockdown of PRL produced embryos with multiple morphological abnormalities. In this study, we explored the function of the PRLR family during embryogenesis and established the zebrafish as a useful model organism to examine embryonic functions of PRL. The combined results (1) define a role for PRL during early embryonic development, (2) provide plausible explanation(s) for the observed phenotypes in PRL-knockdown embryos, and (3) provide a foundation for the direction of future research using zebrafish as a model for studying physiological roles and molecular mechanisms of the PRL superfamily in vertebrates.
Keywords: Endocrinology; Developmental biology; Molecular biology; Embryonic development; Morpholino; Organogenesis; Prolactin; Prolactin receptor; Zebrafish; Biology, Molecular; Prolactin--Research; Zebra danios as laboratory animals; Zebra danios--Embryology